EKSTENSI SIMBOLIK AKTIVISME KOMUNIKASI POLITIK (Refleksi Pertukaran Songkok Bone Jokowi dan Blangkon Jusuf Kalla pada Sidang Tahunan MPR, 16 Agustus 2017) - Abdul Halik (Ilmu Komunikasi UIN Alauddin Makassar, 2017)
The objective classical approach dominates the theory and research of political communism. However, the increasingly dynamic practice of political communications encourages the emergence of other, more interpretive and subjective views. In practice, political communication activism takes place in diverse cultural contexts and therefore a variation of symbols in conveying political messages is required. The symbols of non-verbal communication are now being used by political actors not only as a complement to verbal communication, but the message-code choices are equally important in the process of political communication.